The Significance of Apolipoprotein-A in the Long-Term Death of Patients with STEMI. (15th January 2022) - Lin, Guoli; Chen, Wen; Dai, Caizhi; Xu, Kaizu
Abstract : Objective . To analyze apolipoprotein-A for its predictive value for long-term death in individuals suffering from acute ST-segment elevation myocardial infarction following percutaneous coronary intervention. Methods . We selected patients suffering from acute ST-segment elevation myocardial infarction who underwent emergency PCI at the Affiliated Hospital of Putian University from January 2017 to August 2019. The patients were divided into a high-Apo-A group and low-Apo-A group, and we observed all-cause deaths of patients in the 2 groups within 2 years. Results . The ROC curve analysis indicated the best critical value for predicting 2-year mortality as 0.8150 (area under the curve was 0.626, sensitivity 75.1%, and specificity 51.9%). There was no statistical difference among the two groups in gender, age, lesion vessel, and comorbidities. The two groups had statistically significant differences in apolipoprotein-B/A, high-density lipoprotein, apolipoprotein-A, and hypersensitivity C-reactive protein. Correlation analysis showed a significant negative correlation between apolipoprotein-A and hypersensitive C-reactive protein. The results of the 24-month analysis indicated the incidence of all-cause mortality as higher in the low-Apo-A group, and Kaplan–Meier survival analysis showed the same trend. Conclusion . Apolipoprotein-A can predict the potential for long-term mortality among individuals having acute ST-segment elevation myocardial infarction.